The impact of bullying and cyberbullying on mental health: a systematic review - Agustiningsih, Nia; Yusuf, Ah; Ahsan, Ahsan; Fanani, Qori (International Journal of Public Health Science (IJPHS), 2024)
Bullying, including cyberbullying, has a devastating impact on mental health, particularly among adolescents. This literature study aims to identify mental health issues caused by bullying and cyberbullying. A systematic review was conducted in the last five years using the keywords "bullying, cyberbullying, mental health, adolescent" and the population, intervention, comparison, outcome, study design (PICOS) framework within Scopus (29 articles), ProQuest (187 articles), Science Direct (193 articles), and SAGE (58 articles) published databases in the last five years using the keywords of “bullying, cyberbullying, mental health, adolescent”. The selected articles are those applying quantitative and longitudinal studies published in 2018-2022 in which study participants were adolescents who had experiences as victims of bullying and cyberbullying. The 25 articles met the inclusion criteria for review. Based on the results of the review of the article, it was found that mental health problems can occur in all roles in bullying and cyberbullying, but the highest is in the role of victim. Mental health problems that occur in victims include anxiety, stress, depression, low self-esteem, suicidal ideation, and suicide attempts. Based on these results, different interventions are needed for the roles involved in bullying and cyberbullying, especially for victims, because psychological problems are more common in victims.